Peptide models XXIX. cis-trans Isomerism of peptide bonds: Ab initio study on small peptide model compound; the 3D-Ramachandran map of formylglycinamide - Baldoni, Hector Armando (2000)
Thermodynamic separations for cis and trans-amides and formylglycinamide range from 0.00 to 4.77 kcal/mol as computed at various levels of theory. The barriers for trans ← cis-isomerization, for the same set of compounds, computed at various levels of theory, were found between 15.69 and 22.67 kcal/mol. The cis- and trans-Ramachandran maps of formylglycinamide are compared and the topology of the ab initio 3D-Ramachandran map is presented for the first time.